«Շահնամեի»-ի Սիավուշ Մասիհայի կերպարի համեմատությունը սեմա-հունական առասպելների հետ - Իրան Լաք (ՀՀ ԳԱԱ հրատ.)
Expanding the of comparative sciences, in particular, mythology and comparative literature especially in recent decades, has demonstrated the capabilities of the Shahnameh in the literary world to emulate sideswipe the boundaries and many of the masterpieces of dramatic, English, and rhapsody literature of the world are compared with different parts of the Shahnameh .
Keywords: Ethnography; Folk literature; Language and Literature